Texture Studies on Chinese Wet Noodles (Hokkien - Style Noodles) - Karim, Roselina (1990)
This study reports the textural evaluation of Chinese wet noodles made from Australian Standard White (ASW) flour, using the Instron Universal Food Tester (Model 1140). Procedures for conducting the instrumental test were set up in the preliminary part of the study. Maximum cutting stress (MCS), percentage of residual force (RF) and tensile stress which denote the internal firmness, elasticity and tensile strength of noodles obtained using cutting blade, compression and tensile attachments respectively, were reliable measures of the textural properties of Chinese wet noodles. These variables were highly correlated to sensory evaluation of firmness,chewiness and tensile strength of noodles (r = 0.93 - 0.99 P<0.0l - P<0.l). The study on the function of various components and conditions in noodle making showed that the texture of Chinese wet noodles were affected by the types and amount of water in the formulation, types and pH of the cooking water, levels of sodium chloride (NaCl), sodium carbonate (Na2C03), potassium carbonate and sodium hydroxide (NaOH) in the formulation and the level of protein in flours. Results obtained from the cutting test alone demonstrated that Chinese wet noodles with maximum internal firmness could be made from ASW flour using a water absorption of 32 - 34% and a dough pH of 10.0. Slightly hard water containing 36 ppm Ca2+ should be used in the formulation. Types and pH of cooking water recommended were hard water (64 ppm Ca2+) and pH 9.0 10.0 respectively. The amount of NaOH needed is 0.40% based on the weight of flour. Based on the results obtained from the compress ion test , Chinese wet noodles with maximum elastic property could be processed from ASW flour using 38% water absorption level and a dough pH of 9.0. Distilled or soft water (0 ppm Ca2+) should be used in the formulation and noodles should be cooked in slightly hard water (36 ppm Ca2+) and pH of cooking water suggested was pH 6.0. The amount of Na2C03 or K2C03 needed is 0.25 - 0.50%, whereas if NaOH was used the amount recommended is 0.20% based on the weight of flour. Fortification of ASW flour using wheat gluten and blending of Prime Hard (PH) to ASW flour increase the level of protein in noodle doughs and hence, improved the textural characteristics of Chinese wet noodles. A strong correlation was observed between protein content of flours and MCS and RF (%) with r=0. 99 (P<0.000l) and r=0.90 (P<0.0l) respectively. No significant differences were seen between MCS of Chinese wet noodles processed from ASW and PH flour blends in the ratio of 55:45, 60:40 and 65:35 (P<0.0l). Stability of dough obtained from farinograph can be used to predict the internal firmness of Chinese wet noodles. This study suggested that to produce the required or desirable textural characteristics of Chinese wet noodles several interrelated factors have to be considered and optimised.